Make : fire : the art and science of working with propane - Deagan, Tim (Maker Media, 2016)
Learn how to safely build projects that burn, poof, "boosh," and flare! This complete reference and hands-on guide to working with propane explains how to create a variety of flame effects projects that can be built with common tools and materials. Starting from the basics, this book explains everything you need to know to safely work with propane. An essential reference for building projects like fire cannons, forge torches and flaming sculpture, Make: Fire explains the history, chemistry, and combustion of propane. Using that knowledge as a foundation, readers can then construct a variety of flame-based project on their own using illustrated, step-by-step instructions provided by the author. With simple tools, you can build a gorgeous flambeau, a torch capable of melting aluminum, or flame effects that ignite jaw-dropping fireballs in the sky. Focusing on safety at every step and written by a licensed Flame Effects Operator, this book provides information that has never been brought together in one place. With this guide, readers will master the fundamental components of almost all propane-based projects and develop the skills they need to create their own flame devices and artworks